2017
DOI: 10.1038/s41598-017-07322-5
|View full text |Cite
|
Sign up to set email alerts
|

Pdx1-Cre-driven conditional gene depletion suggests PAK4 as dispensable for mouse pancreas development

Abstract: Constitutive depletion of p21-activated kinase 4 (PAK4) in the mouse causes embryonic lethality associated with heart and brain defects. Given that conventional gene depletion of PAK1 or PAK3 caused functional deficits in the mouse pancreas, while gene depletion of PAK5 or PAK6 did not, we asked if PAK4 might have a functional role in pancreas development. We therefore introduced conditional, Pdx1-Cre-mediated, pancreatic PAK4 gene depletion in the mouse, verified by loss of PAK4 protein expression in the panc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
1
4
1
Order By: Relevance
“…Whereas PAK4 has been shown to be overexpressed in many cancers, including pancreatic cancer, and plays an important role in its growth/invasiveness (64,84), no studies have reported its expression in pancreatic acini. One study reported no expression (73), whereas another study reported PAK4 present in the pancreas, but did not state where it was in the pancreas (88). Our results demonstrate that the only Group-II PAK present in pancreatic acinar cells is PAK4.…”
Section: Discussioncontrasting
confidence: 75%
“…Whereas PAK4 has been shown to be overexpressed in many cancers, including pancreatic cancer, and plays an important role in its growth/invasiveness (64,84), no studies have reported its expression in pancreatic acini. One study reported no expression (73), whereas another study reported PAK4 present in the pancreas, but did not state where it was in the pancreas (88). Our results demonstrate that the only Group-II PAK present in pancreatic acinar cells is PAK4.…”
Section: Discussioncontrasting
confidence: 75%
“…This result suggests that PAK1 and PAK4 play divergent roles in the regulation or maintenance of an "epithelial" or "mesenchymal"-like state in cancer progression, and is consistent with a recent report that expression of PAK1 and PAK4 is associated with different outcomes in pancreatic cancer patients [23]. PAK1 and PAK4 also play different roles in pancreatic function, as PAK1 depletion causes deficits in glucose clearance [24], while PAK4 depletion does not alter pancreas development or function [25].…”
Section: Discussionsupporting
confidence: 91%
“…Transgenic mice with constitutive PAK4 gene depletion do not survive past embryonic day 11.5 16,32,33 ; therefore conditional gene depletion strategies have been developed in the field to study its role in different organs development 33 . Conditional depletion of PAK4 in heart, vasculature, and brain caused severe defect during embryonic development while PAK4 depletion in pancreas did not cause any evident defect in the pancreatic tissue development and function 32,33,42,43 . However, the potential function of PAK4 in mammary gland development has remained unclear.…”
Section: Discussionmentioning
confidence: 94%